Opting Out of Maxim in Quora Q&A Social Media - Ammar Rasyid; Zuindra Zuindra; Mayasari Mayasari (Jurnal Pendidikan dan Sastra Inggris, 2024)
Researcher investigate how to be able to carry out conversations efficiently and effectively in computer-based media using Grice's cooperative principle theory. Researcher use the Qualitative method. The researcher took one of the questions in Quora Indonesia "Mengapa dosen atau pihak kampus tidak melarang mahasiswa ikut demo?", the answer to this question was used as the object of study. The results of this study reveal that there are types of Non-observance of the maxim, namely opting out of a maxim in 9 (100%) of the 17 answers: opting out of maxim quantity (22%), opting out of maxim quality (22%), opting out maxim relevance (22%), opting out of maxim manner (33%).